Zopim Chat Sebagai Bentuk Konvergensi Teknologi Digital Pelayanan Customer Service - Mubarok Ahmadi (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2018)
Digital convergence present in ministry along with the development of information and communication technology (ICT), with the use of technology tools of communication and information technology will be realized excellent service. One way is to utilize the chat facility capable memediasai between businesses and consumers, today's chat software has evolved from facebook messenger, whats up, yahoo Messeger and others. In order to realize excellent service to consumers should be selective in choosing a software company chat. Zopim chat either because the software is integrated with the company's website so that cases of fraud in the online world can be minimized.